Rancangan Ikat Pinggang Ultrasonik untuk Membantu Tunanetra Berjalan dengan Arduino Uno R3 dan Modul HC-SR04 - Aldisa, Rima Tamara; Abdullah, Mohammad Aldinugroho; Maulana, Pandu (Forum Kerjasama Pendidikan Tinggi, 2022)
Blind is a condition of a person who has a disturbance in his vision, obstacles in seeing. The blind are divided into two categories, those who are totally blind and those with residual vision. For this problem, we need an assembly tool that is smart, automatic and makes it easier for blind people and can assist in the activities of a blind person in walking and help tell if there is an object in front of him, this tool will emit a loud sound sensor so that the blind person can hear it. The author designed an Ultrasonic Belt to help the Blind Walk with Arduino Uno R3 and the HC-SR04 Module by using a proximity sensor to determine the presence of objects in front of it, the buzzer immediately emits a sound with a minimum or closest distance of 1 cm and the furthest distance of 1.5 meters is still detected if there are objects in the area. in front of him.